Dermestidae (Coleoptera) from Peru: revision and new records - Díaz, Walter Ciro (2008)
In the present work, the knowledge of Dermestidae from Peru is actualized and the characters for their recognition are given, as well as distribution data and food substrates of nine species, with six new records for Peru Dermestes frischii Kugelann, Trogoderma angustum var. alfa (Solier, 1849), Trogoderma anthrenoides (Sharp, 1902), Attagenus fasciatus (Thunberg), Orphinus fulvipes Guérin-Ménéville; Trogoderma anthrenoides (Sharp, 1902) and Trogoderma inclusum Le Conte, 1854.